Theory for High‐Angular‐Resolution Photoelectron Holograms Considering the Inelastic Mean Free Path and the Formation Mechanism of Quasi‐Kikuchi Band. Issue 11 (23rd July 2020) - Matsushita, Tomohiro; Muro, Takayuki; Yokoya, Takayoshi; Terashima, Kensei; Kato, Yukako; Matsui, Hirosuke; Maejima, Naoyuki; Hashimoto, Yusuke; Matsui, Fumihiko
Abstract : In recent years, highly accurate measurements of photoelectron holograms have become possible through the development of electron energy analyzers with an energy range of 300–1000 eV. Effects of the inelastic mean free path (IMFP) and thermal vibration became apparent in the hologram pattern. For example, the quasi‐Kikuchi band is clearly observed, which cannot be explained by conventional multiple scattering theories. Herein, the theory of photoelectron holograms is summarized, considering the inelastic scattering (IES) and thermal vibration effects. Furthermore, the simulated hologram is compared with a diamond hologram measured at a kinetic energy of 563.4 eV. It is also shown that the formation mechanism of the quasi‐Kikuchi band differs from that of the normal Kikuchi band. Abstract : In recent years, highly accurate measurements of photoelectron holograms have become possible with an energy range of 300–1000 eV. A theory of photoelectron holograms considering the inelastic scattering and thermal vibration effects is developed. The formation mechanism of the quasi‐Kikuchi band is shown as differing from that of the normal Kikuchi band.